Mangrove vegetation diversity after tsunami in east coastal area of Nangroe Aceh Darussalam (Biodiversitas Journal of Biological Diversity, 2007)
It has been conducted the research on mangrove vegetation diversity after tsunami in East Coastal area of Aceh. The method used square method. Amount of mangrove species at tree growth stage was consisted of 9 species. Rhizophora mucronata has the highest important value index (118.62%). The density of mangrove at tree growth stage was 118 tree./hectare, the diversity index was H =1.67. Amount of mangrove species at sapling growth which was found consisted of 10 species. R. mucronata has the highest important value index (138.28%). The density at sapling growth stage was 633 sapling/hectare, the diversity index was H =1.78. The growth of mangrove at seedling stage was consisted of 10 species. It shows that R. mucronata has the highest important value index (50.92%). The densitymangrove at seedling growth stage was 4925 seedling/hectare, the diversity index was H =2.13.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove, diversity, coastal